AN EVALUATION OF ONLINE ARCHITECTURE DESIGN STUDIOS DURING THE COVID-19 PANDEMIC - Widiyani Widiyani; Yorangga Citra Arundati; Margaret Yudhia Aditama; Witriani Witriani (LANGKAU BETANG: JURNAL ARSITEKTUR, 2023)
During the "lockdown" of the COVID-19 pandemic from March to August of 2020, everyone was required to work and study online from home and limit social interaction.  For architecture schools to transfer lecture activities online is challenging. This is because the majority of architecture school courses are studio-based with an emphasis on teachers directly reviewing student work and providing feedback in the form of scribbles. Additionally, site visits are necessary throughout the design process. The purpose of this paper is to gain a deeper understanding of the significant aspects of online design studios from the perspective of first- and second-year undergraduate architecture students during the pandemic. In an online survey, students were asked about their opinions of online design studios and their preference for online or hybrid design studios (a combination of online and limited face-to-face studios) in the following semester. According to the findings of the study, respondents have varying preferences for online design studios based on the length of their studies and the drawing technique used for their assignments. The evaluation identifies three significant aspects of online design studios: the studio system, the supervision process, and the media and facilities. EVALUASI STUDIO DESAIN ARSITEKTUR ONLINE SAAT PANDEMI COVID-19Selama "lockdown" pandemi COVID-19 dari Maret hingga Agustus 2020, semua orang diharuskan bekerja dan belajar secara daring dari rumah serta membatasi interaksi sosial. Dalam pendidikan arsitektur mentransfer kegiatan perkuliahan secara online merupakan hal yang sulit. Hal ini dikarenakan mayoritas mata kuliah sekolah arsitektur berbasis studio, dengan penekanan pada dosen yang meninjau langsung hasil karya mahasiswa dan memberikan umpan balik berupa coretan. Selain itu, kunjungan ke lokasi diperlukan selama proses desain. Tujuan dari makalah ini adalah untuk mendapatkan pemahaman yang lebih dalam tentang aspek signifikan dari studio online dari perspektif mahasiswa arsitektur sarjana tahun pertama dan kedua selama pandemi. Survei online menggunakan skala Likert dan pertanyaan terbuka dilakukan untuk menanyakan pendapat, 178 mahasiswa tentang studio online dan preferensi mereka untuk studio online atau studio hybrid (gabungan studio online dan studio tatap muka terbatas) pada semester berikutnya. Menggunakan analisis deskriptif, data menunjukkan responden memiliki preferensi yang berbeda-beda untuk studio online berdasarkan lama studi mereka dan teknik menggambar yang digunakan untuk tugas mereka. Evaluasi mengidentifikasi tiga aspek signifikan dari studio online: sistem studio, proses pengawasan, dan media dan fasilitas.